the implementation of e-government to improve public service (the development website ub.ac.id in brawijaya university) - Sendy, Kurnias Intanomaya (Jurnal Administrasi Publik, 2013)
In 2001,Brawijaya university using E-Government through website ub.ac.id and PPTI as the founder and the developers of this website. The purpose of this study is to describe and analyze the Implementation of E-Government to Improve Public Service through the development website ub.ac.id and find out supporting and inhibiting factors. This study use descriptive methods and qualitative approach. The results of this study is the implementation of website ub.ac.id has been running based on the level of public services consisting of : information, interaction, transaction and integration but the integration is not perfect yet and there are a few samples of the websites that do not meet all three points. There inhibiting factors are less sharpness, coordination, socialization, awareness and no rule/sanctions. The suggestion given are doing sustainably socialization, there should be strict rules, Â and the students should give critique or suggestions. Â  Keywords: Electronic government, Implementation policy